Learn from failures and stay hopeful to GPR40, a GPCR target with robust efficacy, for therapy of metabolic disorders - Guan, Hong-Ping; Xiong, Yusheng (Frontiers in Pharmacology, 2022)
GPR40 is a class A G-protein coupled receptor (GPCR) mainly expressed in pancreas, intestine, and brain. Its endogenous ligand is long-chain fatty acids, which activates GPR40 after meal ingestion to induce gut secretion of incretins, including GLP-1, GIP, and PYY, the latter control appetite and glucose metabolism. For its involvement in satiety regulation and metabolic homeostasis, partial and full GPR40 agonists had been developed for type 2 diabetes by many pharmaceutical companies. The proof-of-concept of GPR40 for control of hyperglycemia was achieved by clinical trials of partial GPR40 agonist, TAK-875, demonstrating a robust decrease in HbA1c (-1.12%) after chronic treatment in type 2 diabetics. The development of TAK-875, however, was terminated due to liver toxicity in 2.7% patients with more than 3-fold increase of ALT in phase 2 and 3 clinical trials. Different mechanisms had since been proposed to explain the drug-induced liver injury, including acyl glucuronidation, inhibition of mitochondrial respiration and hepatobiliary transporters, ROS generation, etc. In addition, activation of GPR40 by full agonists in pancreas was also linked to β-cell apoptosis in rats. Notwithstanding the multiple safety concerns on the development small-molecule GPR40 agonists for type 2 diabetes, some partial and full GPR40 agonists are still under clinical development. Here we review the most recent progress of GPR40 agonists development and the possible mechanisms of the side effects in different organs, and discuss the possibility of developing novel strategies that retain the robust efficacy of GPR40 agonists for metabolic disorders while avoid toxicities caused by off-target and on-target effects.